1989
DOI: 10.1002/eji.1830190421
|View full text |Cite
|
Sign up to set email alerts
|

T cell responses to fractionated Mycobacterium leprae antigens in leprosy. The lepromatous nonresponder defect can be overcome in vitro by stimulation with fractionated M. leprae components

Abstract: Protective immunity against Mycobacterium leprae is dependent on M. leprae-reactive T lymphocytes. M. lepare-directed T cell reactivity is high in the localized tuberculoid form of leprosy but specifically absent in the disseminated lepromatous type of the disease. Two important questions that are relevant for the understanding of the immune response in leprosy as well as for the design of rational immunoprophylaxis and -therapy strategies are: (a) what are the antigens that trigger T cell responses in tubercu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
29
0

Year Published

1989
1989
2003
2003

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 25 publications
7
29
0
Order By: Relevance
“…As noted above, a majority of such patients can be immunized therapeutically to clinically upgrade their immune responses to M. Ieprae and, in some cases, cure their infection (11). Lymphocytes from a third of lepromatous patients studied, although unresponsive to intact M. leprae, have been reported to be able to respond to electrophoretic fractions of M. leprae extracts (26). These findings are most consistent with the interpretation that suppression is one mechanism of peripheral tolerance in leprosy.…”
Section: Methodssupporting
confidence: 72%
“…As noted above, a majority of such patients can be immunized therapeutically to clinically upgrade their immune responses to M. Ieprae and, in some cases, cure their infection (11). Lymphocytes from a third of lepromatous patients studied, although unresponsive to intact M. leprae, have been reported to be able to respond to electrophoretic fractions of M. leprae extracts (26). These findings are most consistent with the interpretation that suppression is one mechanism of peripheral tolerance in leprosy.…”
Section: Methodssupporting
confidence: 72%
“…Several lines of evidence suggest that the M. leprae-specific T-cell nonresponsiveness observed in LL patients is not due to an absence ofM. leprae-reactive T cells or to defective antigen presentation as claimed in earlier reports (10,11) but may be due to active down-regulation of M. leprae-specific T-cell responses, presumably by suppressor T (Ts) cells induced by M. leprae (12)(13)(14). Supporting this latter premise, we and others have previously isolated CD4+ and CD8+ T-cell clones from the peripheral blood and skin lesions of LL patients and shown that these T cells specifically suppress mycobacterium-specific T-cell responses in vitro (15)(16)(17).…”
mentioning
confidence: 86%
“…bovis bacille Calmette-Guerin (BCG)-vaccinated individuals against Myco. leprae recombinant proteins [11][12][13] and induction of cytotoxic T lymphocytes by the recombinant 65-kD heat shock protein (hsp65) of Myco. bovis BCG have been demonstrated [14][15][16].…”
Section: Introductionmentioning
confidence: 99%